2019
DOI: 10.20473/j.djmkg.v52.i3.p154-158
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Moyers and Tanaka-Johnston analyses for the Arab population of Pekalongan, Indonesia

Abstract: Background: The Moyers and Tanaka-Johnston analyses, both of which were developed through research into the Nordic-Caucasoid population, constitute the most widely used non-radiographic mixed dentition analyses. Application of these prediction methods to other populations has been extensively investigated, although their suitability to the Arab population resident in Indonesia has rarely been studied. Purpose: This study aimed to investigate the reliability of Moyers and Tanaka-Johnston analyses of the Arab po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The concern shared by most authors who studied the method is that due to its greater use in the North European population, the method's reliability for analysis in other ethnicities could be dubious. In a study by Handayani and Hidayah 19 , who assessed the applicability of the method in an Arab population, showed a statistically insignificant difference between the actual values and those predicted by this method. This does not concur with the findings of Lee-Chan et al in an Asian-American population, who found Tanaka Johnston to overestimate the size of smaller unerupted canines and premolars and underestimated larger canines and premolars.…”
Section: Discussionmentioning
confidence: 96%
“…The concern shared by most authors who studied the method is that due to its greater use in the North European population, the method's reliability for analysis in other ethnicities could be dubious. In a study by Handayani and Hidayah 19 , who assessed the applicability of the method in an Arab population, showed a statistically insignificant difference between the actual values and those predicted by this method. This does not concur with the findings of Lee-Chan et al in an Asian-American population, who found Tanaka Johnston to overestimate the size of smaller unerupted canines and premolars and underestimated larger canines and premolars.…”
Section: Discussionmentioning
confidence: 96%
“…4 As a result, our work was aimed at applying their principles to Syeda Areeba Rehan et al The MDWs of permanent teeth differ between groups based on race and ethnicity. 6,8,9,11,12 When compared to demographic groups from India, Indonesia, Saudi Arabia, Syria, Taiwan and Nepal, our sample had smaller mean values for the mesiodistal lengths of canines, premolars, and mandibular incisors. 4,8,[11][12][13] One study from Pakistan's Sindh province did not identify any significant variations in tooth size between genders.…”
Section: Discussionmentioning
confidence: 75%
“…6,8,9,11,12 When compared to demographic groups from India, Indonesia, Saudi Arabia, Syria, Taiwan and Nepal, our sample had smaller mean values for the mesiodistal lengths of canines, premolars, and mandibular incisors. 4,8,[11][12][13] One study from Pakistan's Sindh province did not identify any significant variations in tooth size between genders. 5 However, our research in the Punjab region found that males had wider MDWs than females.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations